THEME AND RHEME ANALYSIS IN THE STUDENTS’ WRITING DESCRIPTIVE TEXT AT A JUNIOR HIGH SCHOOL - Carolus Novanda Hulando Duha; Johannes Jefria Gultom (LINGUISTIK TERAPAN, 2022)
The aims of this study were to describe types of themes and thematic progression patterns found in students’ descriptive texts. This study was conducted by using descriptive qualitative design. The data were collected by using documentation and interview technique. The data were in the form of clauses from students’ descriptive texts at SMPN 1 Delitua. In this study, it was found that there were 267 clauses and 145 types of thematic progression patterns of 20 students’ descriptive texts. The first finding of this study indicate that Unmarked Simple Theme (UST) held the highest frequency of occurrence at 78%, followed by Unmarked Multiple Theme (UMT) at 11.5%, Marked Multiple Theme (MMT) at 7.5%, and Marked Simple Theme at 3%. The second finding of this study indicate that Constant Theme Progression (CTP) held the highest frequency of occurrence at 62.08%, followed by Simple Linear Progression (SLP) at 28.27%, Split Rheme Progression (SRP) at 6.9%, and Derived Hyper-Theme Progression (DTHP) at 2.75%.